Ekora NTT Editorial Team's Strategy in Improving News Quality - Oncijaru, Sisilia Jaru; Kedoh, Lodowik N.; Bastian, Mayelus Dori (IJESS International Journal of Education and Social Science, 2024)
This research explores the editorial strategies implemented by the editorial team of Ekora NTT, a local media in East Nusa Tenggara, in improving news quality in the digital era. Using a descriptive qualitative approach, this research analyses the news production process that involves multiple fact verifications, the use of supporting technology, and continuous training. Data were obtained through in-depth interviews, internal document analysis, and direct observation. The findings show that these strategies significantly improve the accuracy and relevance of news despite challenges such as limited human resources and infrastructure. These results support previous literature, including studies by Hermida (2019) and Newman et al. (2022), which highlight the importance of synergy between technological innovation and capacity building of journalists in maintaining news quality. This research contributes to the development of mass communication theory and provides practical recommendations for other local media in addressing similar challenges. By adopting similar strategies, local media are expected to continue to act as a credible and relevant source of information for the public.